Portrayal of female political aspirants in selected Nigerian newspapers: revisiting underrepresentation and misrepresentation (2012)
Most studies of print media portrayal of women show that there is a general bias against: not only are women under-represented, they are also negatively portrayed. But there is an emerging body of studies that challenge this dominant position, and suggest that the portrayal of women is gradually changing. This study queries the print media portrayal of women in politics in Nigeria focusing on the 2007 and 2011 general elections. Through a content analysis of 4, 386 political stories, selected from The Guardian, This Day and Tell, with deeper focus on the 337 stories that dealt with women contestants, the study found evidence of less but not negative representation of women. Females aspirants were generally portrayed as competent (87.8%) than as incompetent (12.2%); they were also shown as not leaning on men for victory (79.5%). More of them (89.7%) were portrayed as leaders than as followers (10.3%). They were also portrayed as professionals- not as those going into politics for want of a better occupation. The study concluded that while there is need for greater media space for women in politics, it is noteworthy that the little attention they receive now is positive